Cargo selectivity of yeast sorting nexins. (3rd January 2017) - Bean, Björn D.M.; Davey, Michael; Conibear, Elizabeth
Abstract : Sorting nexins are PX domain‐containing proteins that bind phospholipids and often act in membrane trafficking where they help to select cargo. However, the functions and cargo specificities of many sorting nexins are unknown. Here, a high‐throughput imaging screen was used to identify new sorting nexin cargo in the yeast Saccharomyces cerevisiae . Deletions of 9 different sorting nexins were screened for mislocalization of a set of green fluorescent protein (GFP)‐tagged membrane proteins found at the plasma membrane, Golgi or endosomes. This identified 27 proteins that require 1 or more sorting nexins for their correct localization, 23 of which represent novel sorting nexin cargo. Nine hits whose sorting was dependent on Snx4, the sorting nexin‐containing retromer complex, or both retromer and Snx3, were examined in detail to search for potential sorting motifs. We identified cytosolic domains of Ear1, Ymd8 and Ymr010w that conferred retromer‐dependent sorting on a chimeric reporter and identified conserved residues required for this sorting in a functional assay. This work defined a consensus sequence for retromer and Snx3‐dependent sorting. Abstract : Yeast sorting nexins direct membrane proteins on different endosomal trafficking pathways, but the number of known cargos is limited, and few sorting signals have been defined. Here, we used a large‐scale imaging screen to find 23 new sorting nexin cargo proteins, and identified cytosolic sequences that are necessary for sorting nexin‐dependent localization and endosomal recycling. This allowed us to define a consensus sequence for Snx3 and retromer‐dependent cargo sorting.